Identifikasi Masalah Meningkatkan Produksi Padi Varietas Siam Saba Di Desa Limamar Kecamatan Astambul Kabupaten Banjar - Abidin, Nor; Syaifuddin, Syaifuddin; Septiana, Meldia (Agroekotek View, 2023)
The increase in the population of Indonesia is 1.36% per year, so it is estimated that in 2020, 35.97 million tonnes of rice will be needed. The average production of superior rice varieties is 2.3 tons.ha-1 with a range of 2-2.5 tons.ha-1 and the average local rice varieties are 1.8 tons.ha-1 with a range of 1.5-2, 4 ton.ha-1.  The purpose of this research is to find out what problems exist in order to increase rice production in Limamar Village, Astambul District, Banjar Regency. This research uses a descriptive method. The research was conducted using the field survey method, this research was conducted in three stages, namely: (i) preparation, (ii) field implementation, (iii) data processing, and report preparation. Data were collected through field surveys as primary data, namely by collecting questionnaire data in Limamar Village. Based on the results of survey research carried out that the problem of increasing rice productivity in Limamar Village can be seen from gender, age, fertilization and pest control.